Herd It in the Gobi: Deserting pastoralism? - Sternberg, T. (2022)
Global drylands host more than USD 1 trillion in resource extraction investments, which serve to reconfigure communities and landscapes. In Mongolia’s Gobi Desert mega-mining brings social challenges and environmental changes that question if nomadic herding and mining can coexist. Whilst company and community conflict are common, nascent frameworks and mediation models suggest alternate ways to resolve the mining–community conundrum. Here we investigate environmental transformations that herders encounter in the presence of the Oyu Tolgoi mega-mine in Mongolia’s Khanbogd soum (district). Using socio-economic and physical data collected through interviews, field studies and climate records, we assessed local engagement and adaptation to largescale mining. Combining qualitative and quantitative methods enabled us to examine the implications of mining for herder lives and lands in an integrated way. This study presents a holistic assessment of the roles of herders, governments and mines in reshaping pastoralism. In our chosen case study, we find that—contrary to common narratives—mining and herding can, and do, coexist in Khanbogd soum, though ongoing challenges exist which deserve critical attention.